Crowding-Out or Crowding-In? Heterogeneous Effects of Insurance on Solidarity - Andreas Landmann; Björn Vollan; Karla Henning; Markus Frölich (Institute of Labor Economics (IZA), 2020)
We analyze whether the availability of formal insurance products affects informal solidarity transfers in two independent behavioral experiments in the Philippines. The first experiment allows for communication, non-anonymity and unrestricted transfers. The second experiment mimics a laboratory setting without communication and preserves anonymity, which minimizes strategic concerns. The introduction of an insurance treatment alters solidarity in both experiments. We find crowding-out effects in the first setting with strategic motives, while there are even crowding-in effects due to insurance availability in the anonymous experiment. These and additional supporting results are in line with crowding-out of strategic, but not necessarily intrinsic motives due to the availability of insurance.
Keywords: O12; Z13; 330; insurance; solidarity; crowding effects; lab-in-the-field experiment; Philippines